PENGARUH PENGUNGKAPAN IDENTITAS ETIS ISLAM, AGENCY COST DAN INTELLECTUAL CAPITAL TERHADAP KINERJA KEUANGAN (STUDI PADA BANK UMUM SYARIAH YANG TERDAFTAR DI OTORITAS JASA KEUANGAN PERIODE 2016-2018) - Mursidah Mursidah; Yunina Yunina; Meutia Zahara (Jurnal Akuntansi dan Keuangan, 2021)
Abstract: This study aimed to examine the influence of the Islamic ethical indentity disclosure, agency cost, and intellectual capital to the financial performance proxied by return on asset (ROA) in Islamic commercial bank in 2016-2018. Secondary data were used from annual report were published on the website etch Islamic bank between 2016-2018. The purposive sampling method using in this research, so there are theerten Islamic banks are object of research. The analytical method used is multiple linier regresstion analysis using the SPSS 20 softwer program. The results of this study shows that partial of the Islamic ethical identity disclosure have not effect on the financial performance proxied by return on asset (ROA) in Islamic commercial bank, the agency cost have effect negative on the financial performance proxied by return on asset (ROA) in Islamic commercial bank, and intellectual capital have effect positif on the financial performance proxied by return on asset (ROA) in Islamic commercial bank in 2016-2018. Keywords: Islamic ethical identity disclosure, agency cost intellectual capital, financial performance and  ROA.